Indium-catalyzed intramolecular hydroamidation of alkynes: an exo-dig cyclization for the synthesis of pyranoquinolines through post-transformational reaction - Balalaie, Saeed; Rominger, Frank (Organic letters, 2017)
An efficient approach for the synthesis of pyranoquinolines through the indium-catalyzed activation of alkynes is reported. Intramolecular hydroamidation of alkynes can proceed through alkyne activation by indium(III) and then 6-exo-dig cyclization, leading to a fused pyran ring with high selectivity, high atom economy, and good to excellent yields. The cyclization was accomplished through the oxygen, not the nitrogen, of the amide functional group.